If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -7 + 4x + 15 = 56 Reorder the terms: -7 + 15 + 2x + 4x = 56 Combine like terms: -7 + 15 = 8 8 + 2x + 4x = 56 Combine like terms: 2x + 4x = 6x 8 + 6x = 56 Solving 8 + 6x = 56 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 6x = 56 + -8 Combine like terms: 8 + -8 = 0 0 + 6x = 56 + -8 6x = 56 + -8 Combine like terms: 56 + -8 = 48 6x = 48 Divide each side by '6'. x = 8 Simplifying x = 8
| (4x-7)+(-12-8x)= | | 3+25x=20x+12 | | 15-4t=4 | | 3+25x=20x-12 | | e^4x=10 | | 2z(z)+20z=0 | | 3+25x=2-0x+12 | | 34+(25x)+(35x)=93 | | 34+(25x)+(35x)=94 | | (1+i)*z*z+2iz-1=0 | | 34+(25x)+(35x)=90 | | 34(25x)(35x)=90 | | 2z+20z=o | | 55-3x=6-10x | | 4x+15=-5x-12 | | 2x-5+57=3x+9 | | 5y+6-9y= | | 9x+17=4x+42 | | 13=4x-15 | | -6+(-1-b)=19 | | m^2+3=4 | | A=-3a-16 | | 3r^2=-45 | | cos(c)+3*sin(c)=2 | | x=22y+39x | | 4x-5=6x+23 | | Log[2](3x+8)=5 | | 3x-2=-5x-6 | | -h^2+15h+50=0 | | -61= | | Y^2=5Y+50 | | 89=28-r |